2022
DOI: 10.26434/chemrxiv-2022-lrj2r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Yeast Display Enables Identification of Covalent Single Domain Antibodies Against Botulinum Neurotoxin Light Chain A

Abstract: While covalent drug discovery is reemerging as an important route to small molecule therapeutic leads, strategies for the discovery and engineering of protein-based irreversible binding agents remain limited. Here, we describe the use of yeast display, a high-throughput protein discovery platform, in combination with noncanonical amino acids (ncAAs) to identify irreversible variants of single-domain antibodies (sdAbs), also called VHHs and nanobodies, targeting botulinum neurotoxin light chain A (LC/A). Starti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…High-throughput experimentation on the yeast surface enables the rapid discovery of inhibitors from large collections while simultaneously yielding data to better inform future hybrid design efforts. The ncAAmediated production of clickable conjugates described here complements and extends prior work from our group to "chemically enhance" binding proteins by introducing photocrosslinkable and proximity-induced crosslinkable groups in binding proteins 23,24 .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…High-throughput experimentation on the yeast surface enables the rapid discovery of inhibitors from large collections while simultaneously yielding data to better inform future hybrid design efforts. The ncAAmediated production of clickable conjugates described here complements and extends prior work from our group to "chemically enhance" binding proteins by introducing photocrosslinkable and proximity-induced crosslinkable groups in binding proteins 23,24 .…”
Section: Discussionmentioning
confidence: 52%
“…20 Here, we used noncanonical amino acid (ncAA) substitutions and copper-catalyzed azide-alkyne cycloaddition (CuAAC) click chemistry to combinatorially vary the attachment site and hCA-targeting warhead. [21][22][23][24] To increase the throughput of hybrid generation, we also established a 96-well plate-based CuAAC protocol that facilitates rapid assembly and evaluation of hybrid construction and properties in parallel. These investigations allowed us to identify hybrids that retain hCA binding and inhibition while differing substantially from the previously described "parent" hybrids in terms of conjugated amino acid, conjugation chemistry, and even the CA-targeting warhead (with some loss of isoform selectivity noted).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast display serves as a powerful platform to engineer proteins and enzymes and supports assays for quantitatively evaluating protein properties including affinity, stability, activity, and specificity (Cherf and Cochran, 2015). Previously, we have shown that chemically expanding yeast-displayed antibodies with ncAAs results in constructs with new properties including bio-orthogonal reactivity, photocrosslinkability, and spontaneous crosslinkability (Alcala-Torano et al, 2022; Islam et al, 2021). Incorporation of a second noncanonical functionality within chemically expanded, yeast-displayed proteins is expected to usher in a broader range of applications such as the preparation of doubly labeled proteins, parallel introduction of two distinct chemical properties such as crosslinkable groups and recognition motifs (for example, post-translational modifications), or additional chemical moieties of fundamental importance or commercial value (Oller-Salvia and Chin, 2019; Zheng et al, 2018b).…”
Section: Resultsmentioning
confidence: 99%
“…Efficient routes to doubly labeled proteins on the yeast surface are expected to enable applications such as FRET to study protein conformation and dynamics; doubly labeled proteins have previously facilitated FRET studies in vitro and in vivo, including on the surfaces of live mammalian cells (Cui et al, 2017;Maurel et al, 2008;Wang et al, 2014;Wu et al, 2012). Beyond bioconjugation strategies, proteins with dual ncAAs can support applications including intramolecular protein stapling, tethering strategies for small molecules or other drug modalities, and simultaneous presentation of two distinct chemistries such as crosslinking chemistries and posttranslational modifications (Alcala-Torano et al, 2022;Bednar et al, 2021;Islam et al, 2021;Meineke et al, 2020;Ren et al;Zheng et al, 2018b). Thus, the emerging dual ncAA incorporation strategies in this work along with the expanding collection of OTSs supporting diverse ncAA incorporation in yeast will streamline the realization of these intricate protein manipulations in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…[65] This concept was extended via incorporation of photoreactive (azido-phenylalanine) and proximity-reactive (O-(2-bromoethyl)-tyrosine) ncAAs adjacent to the binding site in single-domain antibodies to create covalent inhibitors of botulinum neurotoxin light chain A. [66] The utility of ncAAs reaches beyond engineered ligands. Expansion of the chemical repertoire of enzymes can enable catalysis of otherwise intractable chemical reactions.…”
Section: Ncaa Incorporationmentioning
confidence: 99%